Effect of porous fin in a plate-fin heat exchanger - Kim, Seo Young; Kim, Jin-Ho; Kang, Byung Ha (American Society of Mechanical Engineers, Heat Transfer Division, (Publication) HTD, 1998)
The present experimental study investigates the impact of porous fin on the pressure drop and heat transfer in a state-of-the-art plate-porous fin heat exchanger. Systematic experiments have been carried out in a simplified model of plate-porous fin heat exchanger at the controlled test environment. The porous fins are made of aluminum-alloy foam materials with several permeabilities and a high porosity. The experimental results show that the porous fins can enhance the performance of plate-fin heat exchangers. The pressure drop and the heat transfer coefficients are significantly affected by the permeability of porous fin. The simple correlations of friction factor and Colburn j-factor are also given for future design purpose.